The use of project management methodologies according to empirical research - Brzozowski, Maciej (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The main purpose of the chapter is to examine, on the basis of empirical research, the perceived manner of project management in organizations, as well as to determine the frequency of application of selected project management methodologies along with an assessment of their usefulness. The first part of the article presents – identified on the basis of literature studies – types and examples of project management methodologies, and in the second – the results of empirical research conducted using a questionnaire among participants of projects implemented in various types of organizations. The study showed that in organizations employing respondents, the methodical manner of project management is most often used, while the most popular project management methodologies were PMBoK, Agile and PRINCE2, and respondents highly rated the usefulness of project management methodologies.